The Effect of Chilgoza Pine Nut (Pinus gerardiana Wall.) on Blood Glucose and Oxidative Stress in Diabetic Rats - Hosseini SA (Dove Medical Press, 2020)
Seyed Ahmad Hosseini,1 Maryam Vali,2 Mohammad Hossein Haghighi-Zade,3 Amir Siahpoosh,4 Reza Malihi5 1Nutrition and Metabolic Diseases Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 2Department of Nutrition, School of Paramedical Sciences, Arvand International Division, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 3School of Public Health, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 4Department of Pharmacognosy, School of Pharmacy, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 5Department of Nutrition, Abadan Faculty of Medical Sciences, Abadan, IranCorrespondence: Reza Malihi Tel +989 166051161Email r.malihi@abadanums.ac.irPurpose: Diabetes can increase oxidative stress in various tissues of the body, and the progress of this process is associated with intensification of the complications of diabetes. The current study purposed to evaluate the protective effect of Pinus gerardiana (PG) seed on oxidative stress induced by diabetes in the liver and serum of streptozotocin (STZ)-induced diabetic rats.Materials and Methods: This interventional study was performed on 36 male Wistar rats. The rats were randomly divided into 6 groups (healthy controls, healthy treated with 3% and 6% (PG), diabetic control, diabetic treated with 3% and 6% (PG) doses). After 6 weeks of intervention, weight, glucose, and oxidative stress parameters in serum and liver including total antioxidant capacity, malondialdehyde, total thiol and superoxide dismutase activity were measured. Data analysis was done by statistical software version 16 and Tukey’s one-way ANOVA tests.Results: Diabetic rats showed significantly higher malondialdehyde and fasting glucose levels (12± 1.2 mmol/L) and significant reductions in fasting insulin serum, weight (− 37%), and activity of superoxide dismutase enzymes, total thiol groups, and total antioxidant capacity of serum and liver (about +49% in liver and +16% in serum) (p < 0.001) compared with the healthy groups. Oral administration of PG nuts to diabetic rats caused a significant reduction in malondialdehyde and fasting glucose levels (− 43%) and weight loss (+15%), and a significant increase in activity of superoxide dismutase enzymes, total thiol groups, and total antioxidant capacity of serum and liver (p < 0.001).Conclusion: The present study concluded that PG can decrease fasting blood glucose, improve insulin resistance, reduce weight loss, and improve oxidative stress indices in the serum and liver of STZ-induced diabetic rats. It is a potential therapeutic food supplement for the treatment and prevention of hyperglycemia and high oxidative stress of diabetes.Keywords: diabetes mellitus, Pinus gerardiana, oxidative stress, blood glucose, rat